Coexpression of CD44-positive/CD133-positive cancer stem cells and CD204-positive tumor-associated macrophages is a predictor of survival in pancreatic ductal adenocarcinoma - Hou, Ya-Chin (Cancer, 2014)
BACKGROUND: The interactions between cancer stem cells (CSCs) and tumor-associated macrophages (TAMs) can promote tumor progression, maintain the CSCs population, and reduce therapeutic effects. The objective of this study was to investigate the coexpression of CSCs and TAMs and its clinical significance in pancreatic ductal adenocarcinoma (PDAC). METHODS: Ninety-six patients with PDAC were included in this study. Tissue microarrays were constructed for immunostaining of the CSCs markers CD44 and CD133 and the TAMs marker CD204. Correlations between the expression of CSCs and TAMs markers and clinicopathologic characteristics or disease progression were analyzed. RESULTS: Expression levels of CD44/CD133 and CD204 were significantly higher in tumor tissues than in normal tissues (P < .0001). The variables associated with survival were high coexpression of CD44/CD133 (P = .000), high expression of CD204 (P = .011), and tumor grade (P = .014). There was a positive correlation between CD44/CD133 and CD204 expression (r = 0.294; P = .004). Survival analysis indicated that high coexpression of CD44/CD133 and CD204 was associated significantly with shorter overall survival (P = .000) and disease-free survival (P = .003). Multivariate analysis revealed that high CD44/CD133 expression was an independent prognostic factor for disease-free survival, whereas high CD204 expression was an independent predictor for both overall and disease-free survival. CONCLUSIONS: Coexpression of CD44/CD133 and CD204 is a useful survival prediction marker for patients with PDAC. Cancer 2014;120:2766–2777. © The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. The clinical significance of pancreatic cancer stem cells and tumor-associated macrophages is explored in patients with pancreatic ductal adenocarcinoma. The results clearly demonstrate that coexpression of 2 cancer stem cell markers (CD44 and CD133) and a tumor-associated macrophage marker (CD204) is a useful prognostic factor for predicting the survival of patients with pancreatic ductal adenocarcinoma after surgery.